Copper (I) Selenocyanate (CuSeCN) as a Novel Hole‐Transport Layer for Transistors, Organic Solar Cells, and Light‐Emitting Diodes. (1st February 2018) - Wijeyasinghe, Nilushi; Tsetseris, Leonidas; Regoutz, Anna; Sit, Wai‐Yu; Fei, Zhuping; Du, Tian; Wang, Xuhua; McLachlan, Martyn A.; Vourlias, George; Patsalas, Panos A.; Payne, David J.; Heeney, Martin; et al.
Abstract: The synthesis and characterization of copper (I) selenocyanate (CuSeCN) and its application as a solution‐processable hole‐transport layer (HTL) material in transistors, organic light‐emitting diodes, and solar cells are reported. Density‐functional theory calculations combined with X‐ray photoelectron spectroscopy are used to elucidate the electronic band structure, density of states, and microstructure of CuSeCN. Solution‐processed layers are found to be nanocrystalline and optically transparent (>94%), due to the large bandgap of ≥3.1 eV, with a valence band maximum located at −5.1 eV. Hole‐transport analysis performed using field‐effect measurements confirms the p‐type character of CuSeCN yielding a hole mobility of 0.002 cm 2 V −1 s −1 . When CuSeCN is incorporated as the HTL material in organic light‐emitting diodes and organic solar cells, the resulting devices exhibit comparable or improved performance to control devices based on commercially available poly(3, 4‐ethylenedioxythiophene):polystyrene sulfonate as the HTL. This is the first report on the semiconducting character of CuSeCN and it highlights the tremendous potential for further developments in the area of metal pseudohalides. Abstract : Copper (I) selenocyanate is successfully synthesized, studied, and applied as a wide bandgap hole‐transporting material in transistors, organic solar cells, and light‐emitting diodes, for the first time. Resulting devices exhibit excellent operating characteristics highlighting the tremendous potential of metal pseudohalides as a new class of highly transparent p‐type semiconductors.